Energía Solar Térmica - Rincón Mejía, Eduardo (My University, 2012)
Life Cycle Costing (LCC) is an economic measure that reflects the benefits accrued by solar usage throughout the lifetime of a solar powered system. This is opposed to a simple initial cost comparison, which does not include lifetime energy consumption and, therefore, typically favors non-renewable alternatives.
Keywords: Energía solar térmica; Solar angle formulations, obstruction shading, thermal energy storage, photovoltaics cell output characteristics, PV system design, water heating systems, daylighting, life cycle costing